Distributed ledger technologies for developing Asia - Benno Ferrarini; Julie Maupin; Marthe Hinojales (Asian Development Bank (ADB), 2017)
This paper takes a first pass at assessing areas of implementation for distributed ledger (or blockchain) technology in the context of development finance. It identifies five use cases, including digital identity, trade finance, project aid monitoring, smart energy, and supply chain management. A discussion of the main benefits, risks and implementation challenges suggests that experimentation with distributed ledger technology can produce immediate significant benefits in some areas, while others require further research and investment, as well as additional technical, infrastructural, or regulatory development. Development lenders can play a role in helping unleash these technologies' positive developmental impact throughout the Asian region.
Keywords: G21; MI3; O33; 330; blockchain; developing Asia; distributed ledger technology; financial technology